Endoscopic Ultrasound–Based Pancreatic Cancer Screening of High-Risk Individuals: A Prospective Observational Trial. Issue 5 (May 2018) - Gangi, Alexandra; Malafa, Mokenge; Klapman, Jason
Abstract : Objectives: Pancreatic cancer (PC), a common cause of cancer death, is rarely diagnosed at an early stage. Early detection of PC may improve outcomes in affected patients. This study evaluated the utility of screening of high-risk individuals (HRIs) using an endoscopic ultrasound (EUS)-only approach to detect early malignant changes. Methods: A prospective PC screening program for HRIs was opened in 2007. Fifty-eight patients have enrolled to date. Patients with normal EUS examinations underwent repeat EUS annually for 5 years. Patients with abnormal EUS underwent fine-needle aspiration (FNA) if a mass/cyst 1 cm or longer was found. Those with cysts/mass shorter than 1 cm or benign FNA underwent repeat EUS in 3 months. If unchanged, patients were followed with magnetic resonance imaging. Results: Thirty-nine patients (67%) had initial normal EUS examinations, and 16 patients completed the 5-year trial. Five patients who initially had a normal EUS developed cysts on subsequent examinations. Of the 24 subjects (41%) with abnormal findings, 3 underwent FNA: 2 consistent with intraductal papillary mucinous neoplasm, 1 with benign cytology. The 21 remaining patients had 1 subcentimeter cyst or more followed by magnetic resonance imaging. No PCs have been detected. Conclusions: Precancerous cysts are frequently detected with EUS in HRI. Whether screening impacts survival in HRIs remains unclear and requires further evaluation in larger multicenter trials.